Effect of a 2-week interruption in methotrexate treatment on COVID-19 vaccine response in people with immune-mediated inflammatory diseases (VROOM study): a randomised, open label, superiority trial - Abhishek, A; Peckham, N; Pade, C; Gibbons, JM; Cureton, L; Francis, A; Barber, V; Williams, JAE; Appelbe, D; Eldridge, L; Julier, P; Altmann, DM; et al. (Elsevier, 2023)
Background Methotrexate is the first-line treatment for immune-mediated inflammatory diseases and reduces vaccine-induced immunity. We evaluated if a 2-week interruption of methotrexate treatment immediately after COVID-19 booster vaccination improved antibody response against the S1 receptor binding domain (S1-RBD) of the SARS-CoV-2 spike protein and live SARS-CoV-2 neutralisation compared with uninterrupted treatment in patients with immune-mediated inflammatory diseases. Method We did a multicentre, open-label, parallel-group, randomised, superiority trial in secondary-care rheumatology and dermatology clinics in 26 hospitals in the UK. Adults (aged ≥18 years) with immune-mediated inflammatory diseases taking methotrexate (≤25 mg per week) for at least 3 months, who had received two primary vaccine doses from the UK COVID-19 vaccination programme were eligible. Participants were randomly assigned (1:1) using a centralised validated computer program, to temporarily suspend methotrexate treatment for 2 weeks immediately after COVID-19 booster vaccination or continue treatment as usual. The primary outcome was S1-RBD antibody titres 4 weeks after COVID-19 booster vaccination and was assessed masked to group assignment. All randomly assigned patients were included in primary and safety analyses. This trial is registered with ISRCTN, ISRCTN11442263; following a pre-planned interim analysis, recruitment was stopped early. Finding Between Sept 30, 2021, and March 7, 2022, we screened 685 individuals, of whom 383 were randomly assigned: to either suspend methotrexate (n=191; mean age 58·8 years [SD 12·5], 118 [62%] women and 73 [38%] men) or to continue methotrexate (n=192; mean age 59·3 years [11·9], 117 [61%] women and 75 [39%] men). At 4 weeks, the geometric mean S1-RBD antibody titre was 25 413 U/mL (95% CI 22 227–29 056) in the suspend methotrexate group and 12 326 U/mL (10 538–14 418) in the continue methotrexate group with a geometric mean ratio (GMR) of 2·08 (95% CI 1·59–2·70; p<0·0001). No intervention-related serious adverse events occurred. Interpretation 2-week interruption of methotrexate treatment in people with immune-mediated inflammatory diseases enhanced antibody responses after COVID-19 booster vaccination that were sustained at 12 weeks and 26 weeks. There was a temporary increase in inflammatory disease flares, mostly self-managed. The choice to suspend methotrexate should be individualised based on disease status and vulnerability to severe outcomes from COVID-19. Funding National Institute for Health and Care Research.